2004
DOI: 10.1557/proc-845-aa6.9
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Titania Submicron-Scale Rod Arrays on Titanium Substrate and In Vitro Biocompatibility

Abstract: Titania submicron-scale rod arrays were fabricated on metallic titanium (t-Ti) surfaces by coating a layer of sodium tetraborate on titanium substrates and subsequent thermal treatment.Thin-film X-ray diffraction analysis indicated that the sodium tetraborate gave rutile (TiO 2 : PDF# 21-1276) submicron-scale rod arrays. The rods in the arrays are parallel to each other in the grain of metallic titanium surface. The titania submicron-scale rod arrays deposited apatite within 7 days after being soaked in a simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Under highly acidic conditions the sulfate ions produced in the course of hydrolysis of titanylsulfate will oxidize the titanium substrates to yield titania. Liu et al [16][17][18] observed rutile crystal rods with preferably grown rutile 110 plane, and Hayakawa et al 19 discussed the mechanism and interpret such rod formation in terms of topotaxy relation between Ti 002 and rutile 110. If this would apply to the present case, the very strong Ti 002 diffraction might induce much stronger and sharper rutile 110 diffraction at 27c .…”
Section: Discussionmentioning
confidence: 99%
“…Under highly acidic conditions the sulfate ions produced in the course of hydrolysis of titanylsulfate will oxidize the titanium substrates to yield titania. Liu et al [16][17][18] observed rutile crystal rods with preferably grown rutile 110 plane, and Hayakawa et al 19 discussed the mechanism and interpret such rod formation in terms of topotaxy relation between Ti 002 and rutile 110. If this would apply to the present case, the very strong Ti 002 diffraction might induce much stronger and sharper rutile 110 diffraction at 27c .…”
Section: Discussionmentioning
confidence: 99%
“…Mixed alkoxide glycolate derivatives (Scheme 1b) were formed by reaction between titanium alkoxides and polymethylene glycols. Several forms of mixed alkoxide glycolate derivatives such as Ti 2 (OBu) 2 (glycolate) 3 and Ti 3 (OBu) 2 (glycolate) 6 have been reported previously [16,18,24]. During agitation and aging at room temperature, titanium alkoxide glycolate derivatives were cross-linked to form the randomly stacked structures of titanium glycolates (Scheme 1c).…”
Section: Formation Of Faceted Microrodsmentioning
confidence: 97%
“…Titania is one of the most extensively studied metal oxides because of its potential applications as photocatalysts, selfcleaning materials, ultrawhite pigments, light scatterers, biocompatible materials and high refractive materials for optoelectronic devices [1][2][3][4][5]. Recently, titania has been tailored in a variety of morphologies and sizes as well as its crystalline phases for specific material properties which are required for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) is one of the most extensively studied metal oxides because of its potential applications as photo-catalyzer, self-cleaning material, ultrawhite pigment, light scatterer, bio-compatible material and high refractive material for optoelectronic devices [1][2][3][4][5], and also in waste water purification [6], in solar cells [7], as a gas sensor material [8], host lattice for phosphors [9] and thermoluminescent applications [10], among others. TiO 2 films have been deposited by different methods, such as ablation laser deposition [11], RF-sputtering [12], sol-gel processes [13], chemical vapour deposition (CVD) [14] and ultrasonic spray pyrolysis (USP) [15].…”
Section: Introductionmentioning
confidence: 99%